2016
DOI: 10.1007/s13311-015-0416-0
|View full text |Cite
|
Sign up to set email alerts
|

Axon Guidance Molecules and Neural Circuit Remodeling After Spinal Cord Injury

Abstract: …once the development was ended, the founts of growth and regeneration of the axons and dendrites dried up irrevocably. Santiago Ramón y CajalCajal's neurotropic theory postulates that the complexity of the nervous system arises from the collaboration of neurotropic signals from neuronal and non-neuronal cells and that once development has ended, a paucity of neurotropic signals means that the pathways of the central nervous system are Bfixed, ended, immutable^. While the capacity for regeneration and plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 97 publications
0
24
0
Order By: Relevance
“…Blockade of laminin-integrin interactions can prevent axon growth in vitro (90) and axon regeneration stimulated in vivo after SCI (19). Diffusible chemorepulsion is mediated by Wnt signaling, semaphorins, netrins, and other molecules that create gradients during development (93,96). Interestingly, semaphorins and netrins can be either repellent or attractive to different axons or even to the same axons depending on combinatorial signaling in growth cones (81,82,93).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
See 1 more Smart Citation
“…Blockade of laminin-integrin interactions can prevent axon growth in vitro (90) and axon regeneration stimulated in vivo after SCI (19). Diffusible chemorepulsion is mediated by Wnt signaling, semaphorins, netrins, and other molecules that create gradients during development (93,96). Interestingly, semaphorins and netrins can be either repellent or attractive to different axons or even to the same axons depending on combinatorial signaling in growth cones (81,82,93).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…Interestingly, semaphorins and netrins can be either repellent or attractive to different axons or even to the same axons depending on combinatorial signaling in growth cones (81,82,93). Roles of these molecules after SCI are being studied (93,96,97). Removal of semaphorins alone or in combination with removal of putative myelin inhibitors is insufficient for spontaneous regrowth of serotonin axons after SCI (98).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…The developing axons of many neurons receive positional information in the form of extracellular Wnt gradients [152,153]. The growing axon is tipped with a highly motile lamellopodial and filopodial structure called the growth cone responsible for detecting and responding to extracellular guidance cues that direct axon outgrowth.…”
Section: Axon Pathfindingmentioning
confidence: 99%
“…Interestingly, many guidance and synaptogenic cues that regulate neural wiring during CNS development also contribute to the remodeling of axonal connections in injured spinal cord. Apart from several extracellular matrices, many guidance molecules like the netrins, semaphorins, the robo/slit family, ephrins, Wnts, and repulsive guidance molecules have been identified and are known to play a role after SCI in mammals (Giger et al., ; Harel & Strittmatter, ; Hollis, ; Jacobi, Schmalz, & Bareyre, ). It has been suggested that inhibitory and chemo‐repulsive axon guidance molecules are likely to play an important role in synaptic stabilization and limitation of neuronal plasticity in adult life.…”
Section: Demyelination and Remyelination After Injurymentioning
confidence: 99%